2011
DOI: 10.1007/s10265-010-0401-y
|View full text |Cite
|
Sign up to set email alerts
|

Primary floral allocation per flower in 12 Pedicularis (Orobanchaceae) species: significant effect of two distinct rewarding types for pollinators

Abstract: For animal-pollinated hermaphrodite plants, the factors that affect floral allocation were usually assigned to extrinsic (environment) and intrinsic ones (resources status). Few studies focused on the effect of rewarding type of plants (pollen vs. nectar and pollen). In this study, we investigated the variation in floral allocation per flower with respect to two distinct rewarding types for pollinators in 12 Pedicularis species in alpine regions, testing for the effects of species, plant size, and elevation si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
(58 reference statements)
1
4
0
Order By: Relevance
“…Interspecific variation in resource allocation to the primary female structure of flowers has previously been associated with intrinsic factors such as breeding systems (Cruden & Lyon ) and phylogeny‐dependent variation in flower size (Teixido et al ). Similar to our results, two independent studies have also reported the importance of climate conditions on the proportion of resource allocation per flower to female function, which decreased with elevation across 12 species of Pedicularis in an alpine habitat (Guo et al ; Zhang et al ). However, these studies are limited in that the effects of elevation on carpel allocation did not consider the history of divergence in the genus.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interspecific variation in resource allocation to the primary female structure of flowers has previously been associated with intrinsic factors such as breeding systems (Cruden & Lyon ) and phylogeny‐dependent variation in flower size (Teixido et al ). Similar to our results, two independent studies have also reported the importance of climate conditions on the proportion of resource allocation per flower to female function, which decreased with elevation across 12 species of Pedicularis in an alpine habitat (Guo et al ; Zhang et al ). However, these studies are limited in that the effects of elevation on carpel allocation did not consider the history of divergence in the genus.…”
Section: Discussionsupporting
confidence: 91%
“…environmental conditions), have so far been little studied and deserve further attention. Two independent studies showed that increasing elevation and subsequent cooler temperatures were associated with more attractive and pollen‐rewarding, male‐biased flowers in 12 species of the hermaphroditic genus Pedicularis on the Tibetan Plateau (Guo et al ; Zhang et al ), likely due to relative scarcity of pollinators (see also Crowley et al for sex allocation patterns under pollen limitation). Likewise, a high reproductive effort by allocating a larger resource pool to seed production seems to be an effective strategy to deal with dry and hot conditions or nutrient‐poor soils (Lloyd & Bawa ; Aragón et al ; Chen et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, some plants are capable of immediate and plastic phenotypic responses that may affect the attractiveness of their flowers to floral visitors. In response to environmental American Journal of Undergraduate Research www.ajuronline.org cues, individual plants may change floral phenotypes via phenotypic plasticity [8][9][10][11] . For example, under wet conditions, Nicotiana quadrivalvis produces larger flowers and greater nectar volume than under control conditions 10 .…”
Section: Introductionmentioning
confidence: 99%
“…2003;Zhang &Wang 2011). The Sino-Himalayan region harbours more than 50% of the Pedicularis species and is an important centre of diversity of the genus (Ree 2001;Wang & Li 2005;Zhang & al.…”
Section: Introductionmentioning
confidence: 99%